Harmonisme Sains Dan Agama Dalam Ilmu Ekonomi Islam Menuju Pembangunan Dunia Yang Berkelanjutan - Anindya Aryu Inayati; Richa Angkita Mulyawisdawati (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
In the last few decades, a global understanding of the significance of using science in harmony with nature for the benefit of sustainable global development has been established and implemented in a number of projects. The notion required by humanity to ensure that all economic operations are balanced and sustainable is found in Islamic economics, or fiqh muamalah. The absence of studies, conversations, and discussions within a philosophical framework, however, ignores all parties to the real purposes and development of Islamic economics. The goal of this study is to examine how science and religion relate to sustainable development. Islamic economics will play a key part in this analysis as a science that is compatible with religious instruction. A library method using philosophical approach and descriptive data analysis was employed in this study. The study's findings demonstrate that the epistemological foundation of Islamic economics suggests that there can be beneficial effects on sustainable development from the coexistence of science and religion. Unfortunately, these theories are not fully applied in society's economic transactions as a whole, which leads to the ongoing danger to ecosystem sustainability posed by environmental degradation caused by industrial waste.